2018
DOI: 10.2147/dddt.s186028
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-glucoside combined with Adriamycin on MCF-7 breast cancer cells

Abstract: ObjectiveBreast cancer has been reported to be a serious disease and a threat to women’s health. 2,3,5,4′-Tetrahydroxystilbene-2-O-β-d-glucoside (THSG) is a bioactive natural compound originating from Polygonum multiflorum Thunb., which has been shown to possess anti-inflammatory and antitumor properties. Adriamycin (ADM) is a chemotherapy agent used in tumor therapy that is limited by its side effects. However, little is known about the synergistic effect of THSG combined with ADM on breast cancer. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…It has been reported that THSG treatment significantly impedes cancer growth and invasion in vitro and in vivo . 16 However, in the present study, the MTS assay results indicated that THSG significantly enhanced the proliferation of DPSCs when the concentration was higher than 1 μM, with no cytotoxic effects at 48 and 96 h ( Fig. 1 A).…”
Section: Discussioncontrasting
confidence: 52%
“…It has been reported that THSG treatment significantly impedes cancer growth and invasion in vitro and in vivo . 16 However, in the present study, the MTS assay results indicated that THSG significantly enhanced the proliferation of DPSCs when the concentration was higher than 1 μM, with no cytotoxic effects at 48 and 96 h ( Fig. 1 A).…”
Section: Discussioncontrasting
confidence: 52%
“…In vivo assays with THSG, using azoxymethane-induced colorectal cancer in rats, induced a 50% reduction in total colonic aberrant crypt foci by the inhibition of NF-κB pathway activation [67]. In MCF-7 breast cancer cells exposed to adriamycin and THSG, the vascular endothelial growth factor/phosphatidylinositol 3-kinase/Akt pathway was inhibited, triggering apoptosis by modulating Bcl-2 and caspase-3 [68].…”
Section: Tetrahydroxystilbenementioning
confidence: 99%
“…Stilbenes, mainly 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG), possessed antioxidative, antitumor, anti-inflammatory, endothelial protective, neuroprotective, and liver-protective activities, etc. [10][11][12][13][14][15][16][17][18][19][20][21]. Anthraquinones were reported to possess many biological activities, including immunomodulating, anticancer, antimutation, antibacterial, anticancer, antioxidant, etc.…”
Section: Introductionmentioning
confidence: 99%